Applied behavioral analysis for the skill performance of children with autism spectrum disorder - Silva, Alan Patricio da; Bezerra, Italla Maria Pinheiro; Antunes, Thaiany Pedrozo Campos; Cavalcanti, Matheus Paiva Emidio; Abreu, Luiz Carlos de (Frontiers in Psychiatry, 2023)
Introduction Autism spectrum disorder (ASD) has characteristics that have been observed to develop over time, such as the difficulty of affective, sensory, and emotional processing, which trigger some problems during childhood, limiting children's development. Applied behavior analysis (ABA) is among the therapeutic approaches for ASD, in which treatment can be tailored according to the patient's objectives. Objective Based on ABA, we aimed to analyze the therapeutic strategy for independence in different skill performance tasks of patients diagnosed with ASD. Method This is a retrospective observational case series study including 16 children diagnosed with ASD who received ABA-based treatment at a therapeutic clinic in Santo Andre city, São Paulo State, Brazil. Individual task performance of different skill domains was registered in the ABA+ affective intelligence® software throughout the 12 months (from January 2021 to January 2022) of routine treatment. Results The evolution of skills was observed between the T0 and T1 intervals, with improved skills over the observed period. Conclusion The strategy based on the ABA methodology improved children's skill performance over the observed period.